2009
DOI: 10.1002/bjs.6601
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of gastrointestinal stromal tumours

Abstract: Background: Over the past decade, gastrointestinal stromal tumours (GISTs) have served as a model for the application of tyrosine kinase inhibitors in the treatment of solid neoplasms. Operative and medical management of GISTs is rapidly evolving, but current guidelines appear restricted to basic non-organ-specific recommendations.Methods: A PubMed search was made of the English literature from 1998 to 2008 for references containing the terms 'gastrointestinal stromal tumours' and 'surgery'. This paper reviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(104 citation statements)
references
References 97 publications
1
98
0
5
Order By: Relevance
“…Our data showed that small GISTs located within 5 cm of the anal verge are ideally treated with trans-anal local resection. Limited resection is theoretically simple and feasible, but the risk of early tumor recurrence caused by incomplete excision has been noted in a previous study [18]. We observed that 47.6% of the total number of patients experienced tumor recurrence or metastasis after local resection, and this rate was higher than that of the abdominoperineal resection (38.5%) and the super-low or low anterior resection (27.3%).…”
Section: Discussionmentioning
confidence: 55%
“…Our data showed that small GISTs located within 5 cm of the anal verge are ideally treated with trans-anal local resection. Limited resection is theoretically simple and feasible, but the risk of early tumor recurrence caused by incomplete excision has been noted in a previous study [18]. We observed that 47.6% of the total number of patients experienced tumor recurrence or metastasis after local resection, and this rate was higher than that of the abdominoperineal resection (38.5%) and the super-low or low anterior resection (27.3%).…”
Section: Discussionmentioning
confidence: 55%
“…предполагается, что GIST происходят из предшественников интерстициальных кле-ток Cajal [2,3,8,10]. при иммуногистохимиче-ском исследовании характерна положительная реакция с антителами к CD117 (>95% случаев), CD34 (60-70%) и c-kit белками (70-85%) [2,3,8,10,11,13,14,15,16]. опухоль характери-зуется наличием капсулы, локальным распро-странением с преимущественным отсутствием тенденции к поражению регионарных лим-фатических узлов и метастазированию [2,17].…”
Section: Discussionunclassified
“…The most typical feature of a duodenal GIST is the formation of a deep ulceration in the mucosa or an intramural mass with a centrally ulcerated umbilication (7). Therefore, bleeding is the most common symptom at presentation.…”
Section: Discussionmentioning
confidence: 99%